2017
DOI: 10.1158/0008-5472.can-17-0109
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mediates Responses to Small-Molecule Drugs Targeting Oncogenic Fusion Kinases

Abstract: Oncogenic kinase fusions of ALK, ROS1, RET and NTRK1 act as drivers in human lung and other cancers. Residual tumor burden following treatment of ALK or ROS1+ lung cancer patients with oncogene-targeted therapy ultimately enables the emergence of drug-resistant clones, limiting the long-term effectiveness of these therapies. To determine the signaling mechanisms underlying incomplete tumor cell killing in oncogene-addicted cancer cells, we investigated the role of EGFR signaling in drug-naive cancer cells harb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 57 publications
6
79
0
Order By: Relevance
“…7A, B; data not shown). While our manuscript was in submission a study, consistent with our findings, showed that RET and EGFR inhibitor combinations worked well against some RET-fusions (Vaishnavi et al, 2017). …”
Section: Resultssupporting
confidence: 84%
“…7A, B; data not shown). While our manuscript was in submission a study, consistent with our findings, showed that RET and EGFR inhibitor combinations worked well against some RET-fusions (Vaishnavi et al, 2017). …”
Section: Resultssupporting
confidence: 84%
“…1619,46 In addition, up-regulation of bypass signaling pathways (e.g., EGFR, RAS, and KIT) have also been reported. 2022,47 …”
Section: Discussionmentioning
confidence: 99%
“…However, the knowledge of bypass resistance mechanisms outlined above suggests potential therapeutic avenues one could pursue. For instance, an approach of co-targeting ROS1 and EGFR could be explored given the preclinical evidence for the role of EGFR in driving acquired resistance as well as adaptive survival response to ROS1-targeted therapy (70, 71). Additionally, an entrectinib-based regimen may soon enter early-phase clinical testing, combining the blockade of ALK/ROS1 and MEK, a critical downstream survival and proliferation pathway (71, 102).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of EGFR signaling—not mediated by activating EGFR mutations at the DNA level—has been reported as a bypass mechanism in HCC78 cells made resistant to crizotinib (63, 69), although not yet validated in the clinic. Interestingly, in ROS1 -rearranged and other fusion kinase-driven cell line models, EGFR activation and signaling appears to serve as an important early adaptive survival response to TKI exposure (70). Another preclinical study has suggested a KRAS G12C mutation as a potential crizotinib resistance mechanism in ROS1 -rearranged lung cancer (71).…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%